2003
DOI: 10.1111/1467-8691.00267
|View full text |Cite
|
Sign up to set email alerts
|

The Risks of Autonomy: Empirical Evidence for the Necessity of a Balance Management in Promoting Organizational Innovativeness

Abstract: For the purpose of promoting innovativeness in organizations, the literature recommends more decentralization of power and more participative leadership as one dimension of empowerment and thus greater situation control for employees. In fact, however, increasing situation control involves specific risks (including co-ordination problems). Without concurrent integration to cushion these risks through orientation, consensus and trust, increasing situation control therefore leads not to a further increase in inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 21 publications
(17 reference statements)
0
58
0
Order By: Relevance
“…The strong positive relationship between job control and creativity, innovation, and personal initiative underscores the importance of granting autonomy and contradicts suggestions that high levels of control might be detrimental (Gebert, Boerner, & Lanwehr, 2003). Employees who have control over working procedures might feel more responsible for their work (Hackman & Oldham, 1975) and develop a more active approach to work (Frese et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The strong positive relationship between job control and creativity, innovation, and personal initiative underscores the importance of granting autonomy and contradicts suggestions that high levels of control might be detrimental (Gebert, Boerner, & Lanwehr, 2003). Employees who have control over working procedures might feel more responsible for their work (Hackman & Oldham, 1975) and develop a more active approach to work (Frese et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Innovativeness is generally characterized as a function of adoption [16], creation [17] or a combination of the two. In other words, an innovative individual or firm tends to be an early adopter of new concepts, products and technologies; tends to develop or create new ideas, concepts and products; or some mix of the two.…”
Section: Defining Innovation and Innovativenessmentioning
confidence: 99%
“…An extensive body of research has shown that participative management -defined as joint decision making or at least shared influence in decision making by a superior and his or her employees (Koopman and Wierdsma, 1998) -offers a variety of potential benefits to the overall school organization and to its employees (Day et al, 2005;Gebert et al, 2003). Nevertheless, studies (Sato et al, 2002) have also indicated that teacher involvement in the decision-making process can generate job-related stress and role ambiguity and can create tension and conflict among teachers, principals, and administrators.…”
Section: Review Of Literaturementioning
confidence: 99%